Finite Element Model Updating of Satellite Sailboard Based on Sensitivity Analysis - Haitao Luo; Wei Wang; Jia Fu; Lichuang Jiao (Shock and Vibration)
The modal analysis of a satellite sailboard finite element model is carried out to accurately investigate the response of a satellite sailboard in a complex loaded space environment through simulation. The basic excitation vibration test of the satellite sailboard is used to perform model matching and a correlation test. Appropriate design variables are selected through sensitivity analysis. Modal analysis data and vibration table excitation test response data are used to modify the finite element model. After optimization, the orthogonality of the simulated vibration mode and experimental vibration mode is good. The low-order frequency errors in the simulation model are less than 5%, the high-order errors are less than 10%, and the modal confidence MAC values are above 0.8. The modal frequency and mode shape are closer to the experimental modal frequency and mode shape, respectively. The simulation and test acceleration response of the modified finite element model of a honeycomb panel are compared under the two conditions of sine sweep and random vibration. The acceleration response curves of reference points are consistent, and amplitude and frequency errors are within acceptable limits. The model updating effect is evident, which provides good reference for research on satellites and other aerospace products.